Educação antirracista e os direitos humanos: desafios na implementação da lei 10.639/2003 nos anos iniciais - Silva, Nayara Cristina Freitas (Universidade Federal de São Carlos, 2025)
This study investigates human rights education and anti-racist education. Although anti-racist education is provided for in legislation such as Law No. 10.639/2003, it still faces several challenges regarding its effective implementation in the school environment, especially in the early years of elementary education. Currently, there is a concerning gap between legal discourse and pedagogical practice, which is marked by the lack of adequate teacher training and social resistance to topics considered sensitive to be addressed in schools. In light of this scenario, the research question emerges: how can we expect the construction of an anti-racist society when the teaching of human rights and the implementation of anti-racist education in schools are systematically neglected? This concern, experienced in practice as a teacher, motivated this investigation into the obstacles faced by other educators when addressing these topics effectively. Therefore, the study has the following specific objectives: (i) to analyze, in light of Law No. 10.639/2003, the teaching of human rights and anti-racist education in the early years of elementary school; (ii) to examine the pedagogical practices adopted by teachers in addressing racial issues and the principles of human rights. The methodology used was qualitative, based on bibliographic review and document analysis, considering authors such as Freire, Candau, Munanga, and Mogilka. As a result, it is understood that a critical teacher education, aligned with school realities and diversity, is essential to transform the school into a space for combating racism and social inequalities.
Anti-racist education and human rights: challenges in implementing Law 10.639/2003 in the early years
Keywords: Anos iniciais; Direitos humanos; Educação antirracista; Formação docente; Lei 10.639/2003; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM